Oxide thickness and S/D junction depth based variation aware OTA design using underlap FinFET. (September 2016) - Nandi, Ashutosh; Saxena, Ashok K.; Dasgupta, S.
Abstract: As the gate lengths of FinFETs are scaled into nano meter regime, spatial variations in oxide thickness ( T ox ) and junction depth ( X j ) of source/drain (S/D) doping profile will largely decide the performance of digital and analog circuits that can fall below or above the desired value. Of particular importance is operational transconductance amplifier (OTA), where the crucial analog figures of merit (FOM) such as differential mode gain ( A DM ), common mode gain ( A CM ) and common mode rejection ratio (CMRR) decide the suitability of its use at nanometer regime. In the present work, we have studied the analog performance variation of low- k (dual- k ) underlap FinFET based single stage OTA with spatial variation in T ox and X j of S/D profile. Enhanced and variation less threshold voltage and mobility of dual-k underlap FinFET due to of better screening of longitudinal field and pronounced volume inversion effect, are studied in detail. It is observed that at 16 nm gate length the best case A DM, A CM and CMRR of low- k (dual- k ) FinFET based OTA are 34.2 dB (42.3 dB), 26 dB m (18 dB m), 68.2 dB (84.2 dB) respectively. Subsequently, the spatial variation of T ox and X j leads to worst case change in A DM and A CM of low- k (dual- k ) FinFET based OTA by −6.8 dB (−2.2 dB) and +28.2 dB m (+31.3 dB m) respectively. The negligible deterioration in A CM of dual- k FinFET OTA transforms into CMRR improvements of 37% at this worst case condition as compared to CMRR of low- k FinFET OTA. Furthermore, with gate length scaling, the FOM and their percentage change with T ox and X j of dual- k FinFET OTA are much better than that of low- k FinFET OTA.